Utility of Dutch Lipid Clinic Network Score to Estimate Prevalence of Familial Hypercholestrolemia in Patients with ST-Elevation Myocardial Infarction - Han Bing, Chow; H. S., Ling; B. K., Chung; L. K., Then; I. X., Pang; L. S., Chen; C. D., Bhavnani; C. T., Tan; Y. Y., Oon; K. T., Koh; Y. L., Cham; A. Y. Y., Fong; et al. (Elsevier B.V., 2021)
Background Hypercholesterolaemia is prevalent in the Malaysian population, and its treatment control rates remain suboptimal1. Familial hypercholesterolemia (FH) is an autosomal dominant condition that leads to accelerated arteriosclerotic cardiovascular disease (ASCVD). The prevalence of FH in the general population worldwide has been postulated to be 1:3132 and 1:100 in the Malaysian community3. It has been proposed that lipid lowering treatment prevents further increase in total cardiovascular risk of FH patients, and this recommendation is extensible for FH patients plus atherosclerotic CAD (coronary artery disease). However, despite its implication in CAD, FH is still an underdiagnosed and undertreated condition2-4. To date, the prevalence of FH in the STEMI (ST-elevation myocardial infarction) population in Malaysia is not studied. Establishing the prevalence of FH among patients with CAD and comparing this with the general population would help future efforts at identifying subjects with FH.